Ask Questions, Get Answers

Want to ask us a question? Click here
Browse Questions
Home  >>  CBSE XII  >>  Math  >>  Model Papers
0 votes

Solve \( \tan^{-1}(x+1)+tan^{-1}(x-1)=tan^{-1}\large\frac{8}{31} \).

Can you answer this question?

1 Answer

0 votes
  • \( tan^{-1}x+tan^{-1}y=tan^{-1}\large\frac{x+y}{1-xy}, xy< 1\)
By taking x+1 in the place of x and x-1 in the place of y in the
formula of \(tan^{-1}x+tan^{-1}y\) we have
Substituting the value in the given eqn., we have
\(tan^{-1}(x+1)+tan^{-1}(x-1)= tan^{-1}\bigg( \large\frac{2x}{2-x^2} \bigg)=tan^{-1}\large\frac{8}{31}\)
\(\Rightarrow\: \large\frac{2x}{2-x^2}=\large\frac{8}{31}\)
\( \Rightarrow\:x=\large\frac{1}{4},8\)
\( x=8\) doesn't satisfying
\( Ans : \: so \: x=\large\frac{1}{4}\)
answered Feb 28, 2013 by thanvigandhi_1
edited Mar 22, 2013 by rvidyagovindarajan_1
Ask Question
student study plans
JEE MAIN, CBSE, NEET Mobile and Tablet App
The ultimate mobile app to help you crack your examinations
Get the Android App